Intellectuals, culture and public policy in France : approaches from the left - Ahearne, Jeremy (Studies in social and political thought, 2010)
This text explores a dimension of French intellectuals practice. After a historical and theoretical overview, it is constituted by a series of case studies exploring policy domains in which strategies for shaping the broad culture of France have been debated and developed.